PENGARUH PENYIMPANGAN AKSIS PADA PENDERITA ASTIGMATISME - Aslih Supriyono; M.Wahyu Budiana; Murni Marlina Simarmata (Akademi Refraksi Optisi dan Optometry Gapopin, 2021)
One of the emergence of complaints of vision in patients with astigmatism with the wrong axis is lack of sharp vision, imperfections (distortion) sharp vision, shaded or appearing double when looking at objects. Determination of the axis of astigmatism can be done with blur and cross cylinder techniques. In this paper, the author uses descriptive data collection with literature, one of which is written by Khurana, A. titled “Comprehensive Ophthalmology